2001
DOI: 10.1111/j.1748-720x.2001.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Girl Who Cried Pain: A Bias against Women in the Treatment of Pain

Abstract: T o the woman, God said, "I will greatly multiply your pain in child bearing; in pain you shall bring forth children, yet your desire shall be for your husband, and he shall rule over you." Genesis 3:16There is now a well-established body of literature documenting the pervasive inadequate treatment of pain in this country.' There have also been allegations, and some data, supporting the notion that women are more likely than men to be undertreated or inappropriately diagnosed and treated for their pain.One par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
105
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(141 citation statements)
references
References 58 publications
16
105
1
1
Order By: Relevance
“…For example it has been found that ethnic group may influence analgesic practice (Todd et al 2000) and older people in surgical settings may also not always fair as well as their younger counterparts (Prose 2007). There is also limited data to support the view that women are more likely to be undertreated for their pain than are men (Hoffmann & Tarzian 2001, McNeill et al 2004.…”
Section: Perioperative Pain Managementmentioning
confidence: 92%
“…For example it has been found that ethnic group may influence analgesic practice (Todd et al 2000) and older people in surgical settings may also not always fair as well as their younger counterparts (Prose 2007). There is also limited data to support the view that women are more likely to be undertreated for their pain than are men (Hoffmann & Tarzian 2001, McNeill et al 2004.…”
Section: Perioperative Pain Managementmentioning
confidence: 92%
“…27,30. The fact that this effect was only found for referrals to psychology/psychiatry might be partially accounted for by the stronger gender connotations of the latter (as compared to other referrals and treatment decisions), i.e., stronger association with the female stereotype. 23,28 . In fact, other authors have suggested that the effects of GP sex on medical practices might be greater in clinical situations that are more strongly associated with gender stereotypes.…”
Section: Predictors Of Non-pharmacological Treatment Prescriptions (Nmentioning
confidence: 99%
“…He worked in the surgicaldressing room of a hospital in an area of London with a large immigrant population, but his dismissal of the pain of fellow-humans is alive and well in clinical settings today. It was not until the 1980s that the under-treatment for pain in minority groups and women began to be addressed, and even today these patients continue to be strongly affected by prejudices about their high threshold for perceiving pain (Green, Anderson, Baker, et al 2003, 277-94 andHoffman andTarzian 2001, 13-27). Debates about the relative sensitivity of different people to noxious stimuli were not merely academic.…”
Section: Resultsmentioning
confidence: 99%